2020
DOI: 10.1186/s41927-020-00167-y
|View full text |Cite
|
Sign up to set email alerts
|

The development of rapidly progressive glomerulonephritis associated with both antineutrophil cytoplasmic antibody-associated vasculitis and anti-glomerular basement membrane nephritis in the course of nontuberculous mycobacterium infection: a case report

Abstract: Background Antineutrophil cytoplasmic antibodies (ANCA) and Anti-glomerular basement membrane (GBM) antibodies often induce rapidly progressive glomerulonephritis (RPGN). Some reports have demonstrated RPGN with the sequential appearance of ANCA then anti-GBM antibodies, suggesting that ANCA may induce the development of anti-GBM antibodies. Whereas, many reports have shown that the development of ANCA is associated with various infectious diseases, such as non-tuberculous mycobacterial infection. Case presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Rapidly progressive glomerulonephritis related to NTM is very rare. We were only able to retrieve two prior case reports of rapidly progressive glomerulonephritis in relation to NTM – one with ANCA-associated vasculitis [ 3 ] and one with double-positive ANCA and anti-GBM [ 4 ] disease. To the best of our knowledge, this is the first case report of atypical anti-GBM nephritis associated with NTM.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly progressive glomerulonephritis related to NTM is very rare. We were only able to retrieve two prior case reports of rapidly progressive glomerulonephritis in relation to NTM – one with ANCA-associated vasculitis [ 3 ] and one with double-positive ANCA and anti-GBM [ 4 ] disease. To the best of our knowledge, this is the first case report of atypical anti-GBM nephritis associated with NTM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies reports suggest that the development of ANCA is associated with Mycobacterium tuberculosis infection. One case report found that a patient with non-tuberculosis Mycobacterium infection developed ANCAassociated vasculitis after one year [14] . The studies indicated that NTM infection may induce ANCA.…”
Section: Discussionmentioning
confidence: 99%
“…Double antibody-positive disease (DAPD), exhibiting antiglomerular basement (anti-GBM) and antineutrophil cytoplasmic antibodies (ANCAs) are auto-antibody mediated small vessel vasculitis with ideal preference to renal and pulmonary systems [ 5 ]. Several factors such as smoking, viral infection, or hydrocarbon compounds could precipitate this disease [ 5 , 6 ]. It is a variant of Goodpasture syndrome (GPS).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GBM disease is characterized by an autoimmune response against the α 3 chain of type IV collagen on the GBM in GPS [ 7 ]. Contrastingly, myeloperoxidase (MPO) and proteinase 3 (PR3) antibodies are features of ANCA-associated vasculitis (granulomatosis with polyangiitis, microscopic polyangiitis, and eosinophilic granulomatosis with polyangiitis) [ 5 ]. ANCA-associated vasculitis (AAV) can include the following features: purpura (granulomatous and nongranulomatous skin lesions), neuropathy, acute renal failure (due to neutrophil infiltration into renal tissue), hemoptysis (due to alveolar hemorrhage and nasopharyngeal/oropharyngeal tract hemorrhage), as well as more nonspecific features, such as arthralgias and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation